Microparticle impact–induced bond strength in metals peaks with velocity - Qi Tang; Yuji Ichikawa; Mostafa Hassani (Proceedings of the National Academy of Sciences, 2025)
Supersonic impact of metallic microparticles onto metallic substrates generates extreme interfacial deformation and high contact pressures, enabling solid-state metallic bonding. Although higher impact velocities are generally believed to improve bond quality and mechanical properties in materials formed by supersonic impact deposition, here we report a peak in bond strength for single microparticle impact bonding, followed by a decline at higher impact velocities. Our in situ micromechanical measurements of interfacial strength for Al microparticles bonded to Al substrates reveal a three-fold increase from the critical bonding velocity (800 m/s) to a peak strength around 1,060 m/s. Interestingly, further increase in impact velocity results in a rapid decline in local interfacial strength. The decline continues up to the highest velocity studied, 1,337 m/s, which is well below the threshold required to induce melting or erosion. We show that a mechanistic transition from material strengthening to intensified elastic recovery is responsible for the peak strength in impact-induced bonding, with evidence linking the intensified elastic recovery to adiabatic softening at high impact velocities. Beyond 1,000 m/s for Al, interfacial damage induced by the intensified elastic recovery offsets the strength gain from higher impact velocities, resulting in a net decline in interfacial strength. This mechanistic understanding shall offer insights into the optimal design of processes that rely on impact bonding.